Graphic design : a concise history - Hollis, Richard (New York : Thames & Hudson, 2011)
"From its roots in the development of printing, graphic design has evolved as a means of identification, information and promotion, to become a profession and discipline in its own right. This authoritative documentary history begins with the poster and goes on to chart the development of word and image in brochures and magazines, advertising, corporate identity, television and electronic media, and the effects of technical innovations such as photography and the computer. A new final chapter in this revised edition covers the international developments and leading practitioners in graphic design over the past ten years, exploring the revolutionary impact of digital technology. With over 800 illustrations fully integrated within the text, this indispensable account is uniquely clear, comprehensive and absorbing."--Jacket
From Graphic Art to Design 1890 to 1914 -- The Avant-Garde and the Origins of Modernism 1914 to 1940 -- National Tendencies until 1940 -- The Designer and the Art Director -- Variants of Modernism in Europe -- Psychedelia, Protest and New Techniques -- New Waves: Electronic Technology
Includes bibliographical references and index
Keywords: Graphic arts -- History; Commercial art -- History; History